PENYELESAIAN SENGKETA BATAS LAUT ANTARA INDONESIA DENGAN NEGARA-NEGARA TETANGGA DITINJAU DARI KONVENSI PBB TAHUN 1982 TENTANG HUKUM LAUT (UNCLOS 1982) - simanjuntak, mangisi (Fakultas Hukum Universitas Kristen Indonesia, 2024)
The settlement of disputes both concerning maritime borders and the interpretation and application of the 1982 UN Convention on the law of the sea has also been regulated in articles 279 to 291 of the UN Convention. Article 279 states about the obligation to resolve disputes by peaceful means that:. States Parties shall settle any dispute between them concerning the interpretation or application of this Convention by peaceful means in accordance with article 2, paragraph 3 of the Charter of the United Nations (United Nations), and to this end shall seek settlement in the manner provided for in article 33, paragraph 1 of the Charter. Article 2, paragraph 3 of the Charter of the United Nations states that all Members shall settle international disputes by peaceful means in such a way that international peace and security, and justice, are not threatened. The dispute in question is all disputes of any kind, including maritime border disputes and disputes over the interpretation and application of the United Nations Convention on the Law of the Sea. Article 33 paragraph 1 of the charter states that: Parties involved in a dispute that if it continues to endanger the maintenance of international peace and security must first seek a solution, namely by means of negotiations. investigation, by mediation, conciliation, arbitration. settlement according to law through regional bodies or arrangements. or by any other peaceful means of their own choosing.